Media Xueci berbasis android untuk pembelajaran kosakata bahasa Mandarin siswa kelas X SMA Negeri 6 Malang - Mardiningrum, Sri Rahayu; Afifah, Lilis; Sakti, Karina Fefi Laksana (2020)
This research and development aims to make a product of Xueci media based on android for Mandarin vocabulary learning of tenth grade students public senior high school 6 Malang. The method used is research and development (R&D) with the development model ASSURE. The data were collected using questionnaire sheet and then analyzed using the percentage descriptive technique. The average from product validtion and testing is 91.4%. Thus, it can be concluded that the Xueci media is very good and worthy to used as a vocabulary learning media for 10th grader.